Frictorq, fabric friction tester: a comparartive study eith kes - Lima, Mário (2009)
Coeficiente of friction is one of the factors involved in the so-called parameter fabric hand its importance justifies the number of contributions give in the past to this problem. more recently, a new laboratory instrument was proposed by the authors for the assessment of tis property. A comparative study with another widely respected instruments, the Kes-friction, is the main purpose of this research.